Disturbed Sleep And Prevalence Of Clinical Insomnia Among Italian Breast Cancer Women: A Pilot Study. - Mazzotti, Eva; Claudia, Sebastiani; Andrea, Botticelli; Paolo, Marchetti (Advances in Social Sciences Research Journal, 2017)
Breast cancer patients frequently reported sleep problems. Limited evidences were found for the effects of radiation therapy, chemotherapy and hormone therapy on sleep quality; also the prevalence of sleep disorders remains unclear. The aims of this study were to measure the prevalence of clinical insomnia among patients with breast cancer and to describe the characteristics of poor sleep; to determine whether patients with clinical insomnia and those without differ in physiological, cognitive, and behavioural habits, and in relation to taking psychoactive drugs and natural remedies to treat sleep problems. Methods: 141 consecutive patients with breast cancer, women, (mean age = 61.81 + 11.64) were required to complete: Insomnia Severity Index (ISI), Sleep Disturbance Questionnaire, Hospital Anxiety and Depression Scale and three measures of cancer severity, curability perception, and quality of life. ISI score >14 was categorised as clinical insomnia. Results: In a fully adjusted logistic regression model clinical insomnia was independently associated with the effort to sleep, mental overactivity, use of psychoactive drugs to control sleep problems, when adjusted for age, lymphoedema, joints pain, tamoxifene, hormone therapy, psychological disease as measured by HADS. Conclusion: patients with clinical insomnia had cognitive preoccupations about sleep and used less frequently psychoactive drugs to treat sleep problems. Despite the limited time for a routine clinical care, the clinicians must posed more attention to recognized and treated sleep problems. Future research must be developed to study the effectiveness of interventions designed to develop and improve habits and behaviours for a better sleep efficiency in patients with poor sleep.